Curvatures of hypersurfaces - Navickis, Kazimieras (Lietuvos matematikos rinkinys, 2010)
In this article we generalize some classical formulas for curvatures of hypersurfaces in the n-dimensional Euclidean space using the homogeneous formulas.
Keywords: hypersurface; Gauss curvature; mean curvature